Isten kertésze – a vallástanár személye - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
God’s Gardener – the Character of the Religion TeacherThis topic is always an actual issue, every generation has to reconsider it. The presentstudy tries to integrate and enumerate the relevant Hungarian Reformed literaturereferring to the subject.The most precious tool/instrument: In the religious education the relationship betweenthe Holy Spirit, the pupil and the teacher is very significant. The latter actslike an important tool in God’s hand, playing a key role when it comes to answeringthe existential questions of the pupils.Two-sided approach: The religion teacher does not simply provide informationthrough lessons, they encourage the right perception of God and the relationshipwith Him, thus their personal relationship with Him should be transparent, andloving kindness should describe how they treat children.“We are visible... we are being tracked, followed.” This subtitle is a quote referring tothe exemplariness of the religion teachers. In an era of paradigm crisis this problemgets even more complex, what kind of patterns and ideals does a Christian schoolprovide? The religion teacher should act like an ideal, an example which is authentic,honest and can admit their own failures.The two secrets of a good educationist: self-understanding and self-identity.Being a good teacher requires profound self-understanding viewing their past, andconscious self-development in the future, Christian 4 dimensional growth .Conclusion. The attitude of a religion teacher influences the social status of thechurch and judgment of the whole Christian community through the pupils. Devoted,committed teachers can make their work fruitful if they engage lifelong learning,while they teach they constantly acquire new knowledge and skills.